Effect of different feeding patterns on carcass characteristics and primal cuts of broilers chickens (2017)
An experiment was conducted to assess carcass characteristics and offals of broilers fed on varying forms of feeding regimes. 240, 1-day old broiler chicks-were randomly allotted to four feeding regimes each in 6 replicates of 10 birds per replicate designated as treatments as follows: ad libitum, twice a day split feeding, thrice a day split feeding and 3 hours restriction feeding. Birds were slaughtered on day 42 to determine the relative weights of the primal cuts and visceral organs. Significant differences (P<0.05) were obtained on carcass parameters' measured. Birds on ad libitum feeding had the highest bled (87.6), dressed (61.9), eviscerated (67.0) and de-feathered weights (82.5%) while the least values were obtained from birds fed thrice a day, though the values were not significantly different (P>0.05) from those of birds on twice a day split feeding regime. Birds fed ad-libitum had the highest drumstick weight (8.84%) and wing percentages (6.73%). The neck percentages were 4.47, 4.22, 3.04 and 2.84 for ad-libitum, twice a day, 3 hour restriction and thrice a day feeding respectively. Liver, abdominal and crop weights were similar (P>0.05) for ad libitum and twice feeding regime but were different (P<0.05) from thrice and restricted feeding regime. Broilers on ad libitum and twice a day feeding regimes gave the best results for carcass, primal cuts and organ weights measured.